PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE FLASH CS6 PADA MATERI KONFIGURASI ELEKTRON - Erani, Friska; Seprianto, Seprianto; Prasetya, Cyndi (KATALIS: Jurnal Penelitian Kimia dan Pendidikan Kimia, 2025)
During the learning process, teachers only use lecture methods and rarely use learning media. This is what makes students feel bored and consider chemistry learning very difficult to learn. Therefore, to increase students' interest in learning, learning media is needed, one of which is interactive learning media based on Adobe Flash CS6. This study aims to determine the feasibility, practicality and attractiveness of the Adobe Flash CS6-based learning media that was developed. This study uses the R&D (Research and Development) method with the ADDIE model which is limited to the Development stage. The instruments used are needs analysis questionnaires, validation sheets of material experts and media experts, practicality questionnaires, and media attractiveness questionnaires. The subjects of the study consisted of 4 chemistry teachers at State Senior High Schools in Langsa City and 90 students. The results of the study indicate that chemistry teachers need android-based learning media on electron configuration material, which is indicated by the results of the material validation feasibility questionnaire obtained an Aiken'V value of 0.879 and the media obtained an Aiken'V value of 0.926 with very valid criteria, the level of practicality obtained 90.41% with very practical criteria and the attractiveness of the media obtained a value of 81.85% with very interesting criteria. Based on the results of the study, it was concluded that Adobe Flash CS6-based learning media is feasible to be used as a learning medium for electron configuration material.Keywords:, Learning Media, Adobe Flash CS6, Electron Configuration